2003
DOI: 10.1523/jneurosci.23-24-08506.2003
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of D1and D5Dopamine Receptors in Motor Activity and Striatal Synaptic Plasticity

Abstract: Stimulation of dopamine (DA) receptors in the striatum is essential for voluntary motor activity and for the generation of plasticity at corticostriatal synapses. In the present study, mice lacking DA D1 receptors have been used to investigate the involvement of the D1-like class (D1 and D5) of DA receptors in locomotion and corticostriatal long-term depression (LTD) and long-term potentiation (LTP). Our results suggest that D1 and D5 receptors exert distinct actions on both activity-dependent synaptic plastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
159
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(172 citation statements)
references
References 54 publications
11
159
1
1
Order By: Relevance
“…These data contrast with reports in rats that the D 1 /D 5 receptor antagonist SCH23390 reduced MDMA-induced hyperactivity (Ball et al, 2003;Bubar et al, 2004). SCH23390, however, also reduces locomotor activity in D 1 KO mice, indicating that the locomotor-reducing effects of SCH23390 may not be due solely to D 1 receptor blockade (Centonze et al, 2003). SCH23390 is an antagonist at both D 1 and D 5 receptors (Lawler et al, 1999), as well as 5-HT 2C receptors (Millan et al, 2001).…”
Section: Discussioncontrasting
confidence: 93%
“…These data contrast with reports in rats that the D 1 /D 5 receptor antagonist SCH23390 reduced MDMA-induced hyperactivity (Ball et al, 2003;Bubar et al, 2004). SCH23390, however, also reduces locomotor activity in D 1 KO mice, indicating that the locomotor-reducing effects of SCH23390 may not be due solely to D 1 receptor blockade (Centonze et al, 2003). SCH23390 is an antagonist at both D 1 and D 5 receptors (Lawler et al, 1999), as well as 5-HT 2C receptors (Millan et al, 2001).…”
Section: Discussioncontrasting
confidence: 93%
“…Synaptic plasticity has indeed been shown to occur at target structures of the VTA, including the NAc (Kombian and Malenka 1994;Li and Kauer 2004;Pennartz et al 1993;Robbe et al 2002;Taverna and Pennartz 2003;Thomas et al 2001), PFC (Otani et al 2003) and amygdala (Bauer and LeDoux 2004;Bauer et al 2002;Fourcaudot et al 2009;Kandel 1998, 2007;Humeau et al 2003;Samson and Pare 2005). DA was shown to modulate plasticity in the striatum (Calabresi et al 2007;Centonze et al 2003;Kerr and Wickens 2001;Pawlak and Kerr 2008;Reynolds et al 2001), the amygdala (Bissière et al 2003), PFC Kolomiets et al 2009) and hippocampus (Frey et al 1989(Frey et al , 1990(Frey et al , 1991Lisman 1996, 1998;Gurden et al 1999) but not in the NAc. Behaviorally, it was also shown that pharmacological manipulations of DA levels in the brain shortly after performance can alter memory consolidation or reconsolidation (Dalley et al 2005;Fenu and Fig.…”
Section: Models Of the Effects Of Dopamine Releasementioning
confidence: 99%
“…Both LTP and LTD are dependent on dopamine input (Calabresi et al, 1996;Centonze et al, 2001;Reynolds and Wickens, 2002), with low dopamine levels apparently favoring LTD and high dopamine levels producing LTP at the corticostriatal synapse (Reynolds and Wickens, 2002). Notably, such LTP is blocked by D1 receptor antagonism (Kerr and Wickens, 2001;Reynolds et al, 2001;Centonze et al, 2003).…”
Section: Gene Regulation Enabling Motor Memory Formation: a Hypothesismentioning
confidence: 99%